The Urgency of Arbitration Failure: Reconceptualizing the Construction of Industrial Relations Arbitration - Yati Nurhayati; Ifrani Ifrani; Nahdhah Nahdhah; M.Yasir Said; Martine Flipse (Jurnal Hukum, 2026)
Industrial relations arbitration remains limited and has not yet become a primary option for disputing parties. The purpose of this study is to reconceptualize Industrial Relations Arbitration with a focus on procedural and institutional reform. This study begins with more fundamental principles, taking into account the dimensions of worker protection and the urgent need for institutional restructuring of Industrial Relations Arbitration. The research method used is doctrinal legal research with a prescriptive-analytical approach, combining conceptual, legal, and case-based approaches. The findings reveal several problems, such as the limited scope of disputes that can be submitted and the scarcity of qualified arbitrators. The reconceptualization of Industrial Relations Arbitration offers a solution by expanding the absolute competence of arbitration forums to cover all types of labor disputes. This will optimize the forum for resolving disputes between employers and workers as well as conflicts between trade unions. Furthermore, restructuring the institutional framework of Industrial Relations Arbitration is crucial. The establishment of a competent and independent arbitration body will increase the attractiveness and quality of dispute resolution, with the fundamental principle of maintaining harmonious and sustainable industrial relations.